Jerzy Potocki w kręgu polityki - Jankowiak, Krzysztof (Studia Europaea Gnesnensia, 2013)
The paper covers the first half of the 20th century, a period of decline in the history of aristocracy, Polish aristocracy in particular. The article is concerned chiefly with count Jerzy Potocki, from the Łańcut branch of the family. It aims to determine the state of knowledge about his relationships with broadly understood politics, including his own political activities in different domains. The basis for the analyses is provided chiefly by various publications, at times including data from unpublished archival sources. The analyses demonstrate the diversification of knowledge and advisability of further research, particularly with archival sources.